Hadith #6069 - Sahih al-Bukhari - Shaddad ibn al-Haad (Sahih al-Bukhari)
The Prophet (ﷺ) said “The most superior way of asking for forgiveness from Allah is: ‘Allahumma anta Rabbi la ilaha illa anta, Khalaqtani wa ana `Abduka, wa ana `ala `ahdika wa wa`dika mastata`tu, A`udhu bika min Sharri ma sana`tu, abu’u Laka bini`matika `alaiya, wa abu’u laka bidhanbi faghfir lee fa innahu la yaghfiru adhdhunuba illa anta.” The Prophet (ﷺ) added. “If somebody recites it during the day with firm faith in it, and dies on the same day before the evening, he will be
Grade: Sahih

Hadith #6086 - Sahih al-Bukhari - Shaddad ibn al-Haad (Sahih al-Bukhari)
The Prophet (ﷺ) said, “The most superior way of asking for forgiveness from Allah is: ‘Allahumma anta Rabbi la ilaha illa anta. Khalaqtani wa ana `Abduka, wa ana ‘ala ‘ahdika wa Wa’dika mastata’tu abu’u Laka bi ni ‘matika wa abu’u Laka bidhanbi; faghfirli fa’innahu la yaghfiru-dh-dhunuba ill a ant a. A’uidhu bika min sharri ma sana’tu.’ If somebody recites this invocation during the night, and if he should die then, he will go to Paradise (or he will be from the peopl
Grade: Sahih